Human papillomavirus in high- and low-risk areas of oesophageal squamous cell carcinoma in China - Shuyama, K (Nature Publishing Group, 2007)
To examine the potential roles of human papillomavirus (HPV) in oesophageal squamous cell carcinoma (ESCC) development, we examined the presence of HPV DNA in paraffin-embedded ESCC tissues collected from two areas with different ESCC incidence rates in China, that is, Gansu (n=26) and Shandong (n=33), using PCR with SPF10 primers, or PCR with GP5+/GP6+ primers combined with Southern blot hybridisation. HPV genotype was determined by the INNO-LiPA HPV genotyping kit. HPV DNA was detected in 17 cases (65%) in Gansu, where ESCC incidence is much higher than in Shandong, where HPV was positive in two samples (6%). HPV genotypes 16 and 18 were detected in 79 and 16% of HPV-positive samples, respectively. Real-time PCR analysis suggested the presence of integrated form of HPV DNA in all the HPV-16-positive samples, but its viral load was estimated to be only <1–2 copies cell(−1). We could not detect HPV 16/18 E6 protein expression by immunostaining in any of the HPV-16-positive samples. Neither p16(INK4a) nor p53 expression was related to HPV presence in ESCCs. Further studies seem warranted to examine the possible aetiological roles of HPV in ESCC.